Taxonomic revision of the monotypic genus Acyphus Heller (Coleoptera: Curculionidae) with comments on infraspecific variation - Lanteri, Analia A.; Del Rio, M. Guadalupe (Zootaxa, 2006)
Acyphus Heller, 1921 is a monotypic genus of Entiminae, Naupactini, ranging in north-central Argentina, southern Brazil, Paraguay and Uruguay. Its single species is mainly associated to trees of the genus Prosopis (Leguminosae), with several species ranging throughout the xerophytic forests of the Chacoan subregion. The genus is easily recognized by the presence of 20 elytral striae and the robust antennae, with strongly dilated scape, compressed from near base onwards. Acyphus renggeri (Labram & Imhoff) -senior synonym of Acyphus funicularis Hellershows variation in the distribution and density of the scaly vestiture of the elytra. There is a morphotype devoid of distinct scales and two squamose morphotypes with different irregular nebulose pattern. The paper includes descriptions of the genus and its only species, habitus photographs, line drawings of genitalia and mouth parts, and a map of distribution.